Urban Expansion, Resource Management, and Climate Adaptation: Rethinking Sustainable Growth in India - Sharma, Ashok (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
India is undergoing significant socio-economic transformations driven by demographic shifts, rapid urbanization, and industrialization, all of which present unique challenges and opportunities for sustainable development. This paper explores the demographic transition occurring in India, focusing on the implications of population growth for urban centers, particularly Tier-II cities, and the sustainability of their development. By evaluating the impacts of industrialization and urban sprawl, this study assesses the environmental strains caused by unchecked growth and the role that innovative, smart solutions can play in addressing climate change and resource degradation. The paper also examines the Nagpur Desert ecosystem as a case study to highlight the specific challenges of managing land, water, and human resources in fragile environments. It argues for a holistic, ecological approach to development that integrates sustainable resource management with social and economic growth. Through these lenses, the paper provides insights into how India can balance the pressures of modernization with the imperative of environmental stewardship.